Universities, Sustainability, and Neoliberalism: Contradictions of the Climate Emergency Declarations - O’Neill, Kirstie (2021)
UK universities have been successively declaring a climate emergency, following the University of Bristol’s lead in 2019. Universities are key actors in climate change education, and potentially progressive organisations researching, teaching and implementing low carbon futures. Using universities’ sustainability strategies, we present a secondary analysis identifying neoliberalism’s significant role in influencing universities’ sustainability policies and practices. This plays out through university boosterism where universities use their sustainability work to claim sustainability leadership, representing a form of sustainability capital to attract funding and potential students. Furthermore, we suggest a cognitive-practice gap exists between those researching sustainability and those implementing sustainability in universities. Thus, we conclude that there are inherent tensions in universities’ sustainability governance, with universities embodying contradictory sustainability discourses and advancing a form of green capital. Entrenched neoliberal ideologies present challenges for those declaring a climate emergency and how such declarations are subsequently operationalised.